DNA methylation and RASSF4 expression are involved in T-2 toxin-induced hepatotoxicity - Liu, Aimei; Xu, Xiaoqing; Hou, Ren; Badawy, Sara; Tao, Yanfei; Chen, Dongmei; Ihsan, Awais; Wang, Xu; Wu, Qinghua; Yuan, Zonghui (Toxicology, 2019)
T-2 toxin is a secondary metabolite produced by Fusarium species and commonly contaminates food and animal feed. T-2 toxin can induce hepatotoxicity through apoptosis and oxidative stress; however, the underlying mechanism is not clear. Recent studies indicated that RASSF4, a member of the RASSF family, participates in cell apoptosis and some cancers due to its inactivation via DNA hypermethylation. However, its role in T-2 toxin-induced liver toxicity is poorly understood. Therefore, in this study, female Wistar rats were given a single dose of T-2 toxin at 2 mg/kg b.w. and were sacrificed at 1, 3 and 7 days post-exposure. A normal rat liver cell line (BRL) was exposed to different concentrations of T-2 toxin (10, 20, 40 nM) for 4, 8, 12 h, respectively. Histopathological analysis revealed with apoptosis in some liver cells and clear proliferation under T-2 toxin exposure. Expression analysis by immunohistochemical assays, quantitative real-time PCR (qPCR) and western blot demonstrated that T-2 toxin activated PI3K-Akt/Caspase/NF-κB signaling pathways. Additionally, DNA methylation assays revealed that the expression of RASSF4 was silenced by promoter hypermethylation after exposure to T-2 toxin for 1 and 3 days as compared to the control group. Moreover, joint treatment of 5-Aza-2'-deoxycytidine (DAC) (5 μM) and T-2 toxin (40 nM) increased expression of RASSF4 and PI3K-Akt/caspase/NF-κB signaling pathways-related genes, inducing cell apoptosis. These ﬁndings for the ﬁrst time demonstrated that DNA methylation regulated the RASSF4 expression under T-2 toxin, along with the activation of its downstream pathways, resulting in apoptosis.
Keywords: Liver; Animals; Real-Time Polymerase Chain Reaction; Rats; apoptóza; vztah mezi dávkou a účinkem léčiva; Female; buněčné linie; Rats, Wistar; játra; Blotting, Western; průtoková cytometrie; Apoptosis; ženské pohlaví; nádorové supresorové proteiny; T-2 Toxin; RASSF4; T-2 toxin; Flow Cytometry; intracelulární signální peptidy a proteiny; metylace DNA; Cell Line; western blotting; Dose-Response Relationship, Drug; Tumor Suppressor Proteins; DNA Methylation; Intracellular Signaling Peptides and Proteins; krysa rodu Rattus; DNA methylation; zvířata; kvantitativní polymerázová řetězová reakce; Hepatotoxicity; potkani Wistar